2022
DOI: 10.3389/fmicb.2022.913718
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Gut Microbiota in Patients With Clear Cell Renal Cell Carcinoma

Abstract: Different gut microbiota is implicated in different diseases, including cancer. However, gut microbiota differences between individuals with clear cell renal cell carcinoma (ccRCC) and healthy individuals are unclear. Here, we analyzed gut microbiota composition in 51 ccRCC patients and 40 healthy controls using 16S rRNA sequencing analysis. We observed that Blautia, Streptococcus, [Ruminococcus]_torques_group, Romboutsia, and [Eubacterium]_hallii_group were dominant and positively associated with ccRCC. We is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…It has been proposed that it is a probiotic that could benefit HCC patients receiving anti-PD-1 immunotherapy as well as combat the anxiety and fear associated with cancer treatment and recurrence ( Okubo et al., 2020 ; Mao et al., 2021 ). Ruminococcus, on the other hand, was strongly associated with some diseases and significantly enriched in patients with thyroid cancer, endometrial cancer, and clear cell renal cell carcinoma, and it may serve as a biomarker for clinical features and prognosis and provide a new therapeutic target for clinical treatment ( Chen et al., 2022 ; Ishaq et al., 2022 ; Zhao et al., 2022 ). In this study, it was discovered that the relative abundances of Ruminococcus and Ruminococcus bicirculans in HCC were significantly lower than those in NC but significantly higher than those in LC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that it is a probiotic that could benefit HCC patients receiving anti-PD-1 immunotherapy as well as combat the anxiety and fear associated with cancer treatment and recurrence ( Okubo et al., 2020 ; Mao et al., 2021 ). Ruminococcus, on the other hand, was strongly associated with some diseases and significantly enriched in patients with thyroid cancer, endometrial cancer, and clear cell renal cell carcinoma, and it may serve as a biomarker for clinical features and prognosis and provide a new therapeutic target for clinical treatment ( Chen et al., 2022 ; Ishaq et al., 2022 ; Zhao et al., 2022 ). In this study, it was discovered that the relative abundances of Ruminococcus and Ruminococcus bicirculans in HCC were significantly lower than those in NC but significantly higher than those in LC.…”
Section: Discussionmentioning
confidence: 99%
“…These five bacterial taxa were able to accurately differentiate between ccRCC patients and healthy individuals with an AUC of 93.3%, suggesting that they could be potential biomarkers for ccRCC. Moreover, in vitro experiments of the study demonstrated that S. lutetiensis, a member of these microbial taxa, promoted the proliferation, migration, and invasion of ccRCC (24). In another study, Heidler et al firstly used 16S rRNA sequencing to detect bacteria in the kidney tissues of 10 RCC patients who underwent laparoscopic nephrectomy and had no history of urinary tract infection in the past 6 months (25).…”
Section: The Relationship Between Renal Cell Carcinoma and Microbiotamentioning
confidence: 99%
“…But higher accuracy can be achieved with a combination of other bacterial species or existing diagnostic methods like fecal immunochemical test (FIT) ( Wong et al, 2017 ; Liang et al, 2021 ). Satisfactory performances of fecal bacterial markers have also been shown for diagnosing pancreatic cancer [area under the ROC curve (AUC) = 0.78–0.94] ( Nagata et al, 2022 ; Kartal et al, 2022 ), lung adenocarcinoma (AUC = 0.76–0.976) ( Zheng et al, 2020 ; Lim et al, 2021 ), cervical cancer (AUC = 0.913) ( Kang et al, 2020 ), hepatocellular carcinoma (AUC = 0.8064) ( Ren et al, 2019 ), clear cell renal cell carcinoma (AUC = 0.933) ( Chen et al, 2022a ), and so on. The diagnostic performance of other diagnostic models based on non-bacterial microorganisms [such as fungal ( Coker et al, 2019 ), archaeal ( Coker et al, 2020 ), and viral ( Nakatsu et al, 2018 ) features] has also been described to discriminate individuals with or without CRC.…”
Section: Clinical Applicationsmentioning
confidence: 99%